2022
DOI: 10.1111/hiv.13299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health conditions among people living with HIV during the COVID‐19 pandemic: A rapid systematic review and meta‐analysis

Abstract: Background The COVID‐19 pandemic has generated many mental health problems worldwide. People living with HIV (henceforth known as PLHIV) bear a higher mental health burden in comparison with the general population. Therefore, their risk of mental health problems may be elevated during the pandemic. Methods We conducted a systematic review and meta‐analysis to assess the prevalence of depression, anxiety, psychological stress, insomnia and loneliness among PLHIV during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
1
18
2
Order By: Relevance
“…Therefore, it is reasonable that analysis of EFV-induced neuropsychiatric adverse events in previous studies was limited by the follow-up durations. As for the prevalence of depression and anxiety, we found higher results (15.6% and 14.615.3`% respectively) compared to that in previous study in 2017 2015 (12.939.6% and 12.849.7% [ 19 ] respectively) in China using HADS, however, our results werelower to contemporaneous reports in 2020 (16.9% and 23.0%) according to a meta-analysis [ 33 ]. The prevalence of depression and anxiety of this study may have different outcomes from other studies worldwide contemporaneously for different reasons: 1) different scales are used.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is reasonable that analysis of EFV-induced neuropsychiatric adverse events in previous studies was limited by the follow-up durations. As for the prevalence of depression and anxiety, we found higher results (15.6% and 14.615.3`% respectively) compared to that in previous study in 2017 2015 (12.939.6% and 12.849.7% [ 19 ] respectively) in China using HADS, however, our results werelower to contemporaneous reports in 2020 (16.9% and 23.0%) according to a meta-analysis [ 33 ]. The prevalence of depression and anxiety of this study may have different outcomes from other studies worldwide contemporaneously for different reasons: 1) different scales are used.…”
Section: Discussioncontrasting
confidence: 90%
“…Four hundred twenty-four PLHIV were enrolled, the mean age was 34 years (IQR, [30][31][32][33][34][35][36][37][38][39][40], 416 (98.1%) were male, and 398 (94.9%) were Han. The mean body mass index (BMI) was 22.8 kg/m 2 (IQR, 20.8-24.7).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Also it was found that depression is highly prevalent among PLWH by representing racial or sexual minorities (Rendina et al., 2018). Finally, recent years have brought about additional global stress in the form of the coronavirus (COVID‐19) pandemic, which particularly hampered the mental functioning of this vulnerable population (Lee et al., 2021). Thus, in the present study, our aim was to examine the trajectories of depressive symptom changes among PLWH during the critical period of the COVID‐19 pandemic and its covariates in the form of perceived HIV/AIDS stigma and emotional support.…”
Section: Introductionmentioning
confidence: 99%
“…Within this latter group we can include PLWH (May & Fullilove, 2022). In light of the recent report (WHO, 2022), during the COVID‐19 pandemic, PLWH have experienced substantial disruptions in their everyday functioning, including barriers to healthcare due to COVID‐19‐exclusive transformations of hospitals, delays in HIV testing, problems with HIV treatment, or a lack of anonymity due to telemedicine services (Lee et al., 2021). In addition, several studies have found that PLWH as a group suffered particularly strongly from disruptions in their social life during the pandemic, including isolation and related depressive and suicidal thoughts (Sun et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation